Tissue quantification of neutral and acid mucins in the mucosa of the colon with and without fecal stream in rats - Nonose,Ronaldo (2009)
PURPOSE: To quantify the intensity of the expression of neutral and acids mucins in mucosa of the colon with and without fecal stream and to correlate this with the duration of fecal transit diversion. METHODS: Thirty male Wistar rats were subjected to fecal transit deviation in the left colon by a proximal colostomy and a distal mucous fistula. The animals were divided into three experimental groups, according to whether sacrificing would be performed six, 12 or 18 weeks after surgery. The expression of neutral and acid mucins was evaluated using the histochemical techniques of Periodic Acid Schiff and Alcian Blue, respectively. The tissue mucins expression was quantified by computer-assisted image analysis software (NIS-Elements) in the segments with and without fecal stream. Student's paired t test was used to compare the quantities of mucins in colon with or without fecal stream and variance between the experimental groups by ANOVA and Newman-Keuls post-test, establishing level of signification of 5% (p<0.05). RESULTS: There were significant decreased quantities of acid and neutral mucins in the colon without transit, compared with the colon with fecal stream, independent of the duration of exclusion. There was increased expression of neutral mucins in the colon with fecal stream after 12 and 18 weeks of exclusion. There was no increase in the expression of acid mucins in the colon with transit as the duration of fecal transit exclusion progressed. There was increased production of acid mucins in the animals submitted to diversion of the fecal stream for 18 weeks, compared with those subjected to diversion for 6 and 12 weeks. In the colon without fecal stream, there was increased expression of neutral mucins after 12 and 18 weeks of exclusion. CONCLUSIONS: Deviation of the fecal stream decreased the expression of acid and neutral mucins in the segments without fecal transit, compared with segments with transit. Regardless of the reduced expression of acid and neutral mucins in the segments without fecal stream, their tissue expression increased with increasing duration of intestinal deviation.